2017
DOI: 10.15290/ose.2017.01.85.08
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age on Polish Households Financial Behavior – Indebtedness and Over-Indebtedness

Abstract: SummaryThe aim of this paper is to examine how age of the head of household affects the financial behavior of households in terms of indebtedness and over-indebtedness. The over-indebtedness was analyzed from two aspects -margin and debt service ratio indicators. The data from Household Budget Survey in 2011 conducted by Central Statistical Office of Poland was used in the analyses. To achieve the main objective, selected measures of descriptive statistics and contingency tables were used. The research results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…Only a minority of households could be considered over-indebted when arrears are taken into account. This is in line with the results from previous, fragmentary studies of Polish households (Świecka 2009;Anioła-Mikołajczak 2017). The percentage of overindebted households in relation to the DSTI30 obtained in our study is similar to the results presented by Świecka (2016) and by the NBP (2017).…”
Section: Discussionsupporting
confidence: 93%
“…Only a minority of households could be considered over-indebted when arrears are taken into account. This is in line with the results from previous, fragmentary studies of Polish households (Świecka 2009;Anioła-Mikołajczak 2017). The percentage of overindebted households in relation to the DSTI30 obtained in our study is similar to the results presented by Świecka (2016) and by the NBP (2017).…”
Section: Discussionsupporting
confidence: 93%
“…Another group of factors relates to the estimates generated by the concept of behavioural finance. A large list of such factors is contained in a number of works by researchers of credit behavior of the population [see, e.g., 1,2,9,10,11,13].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the study by Mpogole et al (2012) in Tanzania revealed that over 70% of the respondents had problems in loan repayment because of having multiple loans. Anioła-Mikołajczak (2017) found out that over-indebtedness in Poland is associated with individuals taking multiple loans from different lenders. Many other researchers have identified a link between over-indebtedness and multiple borrowing (e.g., Haq et al, 2018a;Wałęga & Wałęga, 2020).…”
Section: Multiple Borrowing and Over-indebtednessmentioning
confidence: 99%